Baccharis coridifolia poisoning in livestock in Uruguay. (December 2020) - Schild, Carlos Omar; Oliveira, Luiz Gustavo Schneider; Miraballes, Cecilia; Giannitti, Federico; Casaux, María Laura; Aráoz, Virginia; da Silva Silveira, Caroline; Boabaid, Fabiana Marques; Riet-Correa, Franklin
Abstract: Baccharis coridifolia is one of the most common poisonous plants affecting livestock in Uruguay. Poisoning occurs when animals raised in areas free of B. coridifolia are transported to pastures containing the plant . Young stock become spontaneously averted to it after ingesting non-toxic amounts of the plant. As B. coridifolia is widespread in the country, farmers selling livestock report when animals have been raised in areas with the plant, meaning that they are naturally averted and will not ingest it if introduced in B. coridifolia -containing paddocks. Of 2456 farmers from 18 departments of Uruguay selling cattle through online auctions between June 2019 and May 2020, 78% mentioned that the animals they were selling were raised in grasslands containing B. coridifolia . However, only 35.8% of the farmers from three departments of Eastern Uruguay mentioned that their cattle were raised in grasslands with B. coridifolia . Herds from these departments presented 16.7 times (95% CI: 13.1–21.3; p < 0.001) more risk of not being naturally averted to B. coridifolia ingestion than the herds of the other 15 departments of the country . In this paper we review all outbreaks of B. coridifolia poisoning reported in livestock in Uruguay from 1911 to present. We also describe three outbreaks of poisoning, one in cattle and two in sheep that were poisoned in the same farms in which the animals were raised. Intoxication occurred when the animals raised indoors and/or in cultivated pastures without B. coridifolia were introduced into grasslands of the same farms containing B. coridifolia . Typical gastrointestinal lesions were observed in pathological examinations. Furthermore, two of three necropsied heifers showed severe acute nephrosis, which had not been reported previously in this poisoning. Highlights: Baccharis coridifolia causes acute poisoning in livestock due to digestive lesions. The plant induces natural aversion in young animals that ingest it in non-toxic amounts. Poisoning occurs when non-averted livestock are introduced in paddocks with the plant. In Uruguay 78% of the herds are raised in grassland with the plant and are averted to it.